Nucleosome dynamics render heterochromatin accessible in living human cells - Hemant K. Prajapati; Zhuwei Xu; Peter R. Eriksson; David J. Clark (Nature Communications)
Abstract The eukaryotic genome is packaged into chromatin, which is composed of a nucleosomal filament that coils up to form more compact structures. Chromatin exists in two main forms: euchromatin, which is relatively decondensed and enriched in transcriptionally active genes, and heterochromatin, which is condensed and transcriptionally repressed. It is widely accepted that chromatin architecture modulates DNA accessibility, restricting the access of sequence-specific, gene-regulatory, transcription factors to the genome. However, the evidence for this model derives primarily from experiments with isolated nuclei, in which chromatin remodeling has ceased, resulting in a static chromatin structure. Here, using a DNA methyltransferase to measure accessibility in vivo, we show that both euchromatin and heterochromatin are fully accessible in living human cells, whereas centromeric α-satellite chromatin is partly inaccessible. We conclude that all nucleosomes in euchromatin and heterochromatin are highly dynamic in living cells, except for nucleosomes in centromeric chromatin.